The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1093/ejo/cjm073
|View full text |Cite
|
Sign up to set email alerts
|

Angles of facial convexity in different skeletal Classes

Abstract: The objective of this study was to investigate whether it is possible to use a lateral (profile) photograph to determine the underlying skeletal Class and which reference points of the angle of convexity are most suitable for this purpose. Profile photographs and lateral cephalographs included in the baseline data for 180 orthodontic patients were retrospectively evaluated. The subjects were assigned to skeletal Classes based on Wits values obtained by radiolographic analysis. The Class I subjects were 58 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 35 publications
3
17
0
2
Order By: Relevance
“…The same authors observed smaller angles for the total face angle (GL-SN-POG) in Class II than in Class I patients, which is in contrast to a reverse observation reported by Ferrario et al 16 Our results did not reveal any significant differences in total face angle for Class II children. In accordance with the findings of Godt et al, 7 however, we did notice higher values (to some extent significantly higher values) for this angle in the Class III patients than in the control group. The values those authors obtained with 95% confidence intervals (173.99u to 176.99u) were very similar to our mean values with standard deviations (168.7u to 175.2u).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The same authors observed smaller angles for the total face angle (GL-SN-POG) in Class II than in Class I patients, which is in contrast to a reverse observation reported by Ferrario et al 16 Our results did not reveal any significant differences in total face angle for Class II children. In accordance with the findings of Godt et al, 7 however, we did notice higher values (to some extent significantly higher values) for this angle in the Class III patients than in the control group. The values those authors obtained with 95% confidence intervals (173.99u to 176.99u) were very similar to our mean values with standard deviations (168.7u to 175.2u).…”
Section: Discussionsupporting
confidence: 93%
“…These questions have not been resolved previously. 5 A number of authors [6][7][8][9][10] did find an association between soft tissue and underlying bone/tooth structures, concluding that information about skeletal and dental abnormalities can be derived from soft tissue architecture. The fact, however, that these studies primarily refer to adults illustrates that pertinent data about younger patients remain to be collected.…”
Section: Introductionmentioning
confidence: 99%
“…Godt et al 7 determined that the convexity angle most suitable for determining skeletal class was the angle subtended by Nasion-Subnasale-Pogonion N'SnPog' landmarks, as defined by Zylinski et al 1 and illustrated in Fig 1. This angle lies in the mid-sagittal plane, excludes the nose and provides an anterior-posterior assessment of the maxilla and the mandible. Manual indication of the angle was originally performed on lateral photographs 7 that provide a silhouette of the apparent midline.…”
Section: Convexity Anglementioning
confidence: 99%
“…Manual indication of the angle was originally performed on lateral photographs 7 that provide a silhouette of the apparent midline. However, with the advent of 3-D imaging, the midline has to be determined from the 3-D manifold.…”
Section: Convexity Anglementioning
confidence: 99%
See 1 more Smart Citation